1976
DOI: 10.1016/0035-9203(76)90128-0
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of BCG against Mycobacterium ulcerans disease: a controlled trial in an endemic area of Uganda

Abstract: In a BCG vaccination trial in an area of Uganda endemic for Mycobacterium ulcerans disease ("Buruli Ulcer"), 8,856 persons were examined for the disease in mid-1970 and tuberculin tested; BCG was given by intradermal injection to a random 50% of all those with negative, low or middle grade tuberculin reactions; Twelve months later the study group was re-examined for M. ulcerans lesions and, subsequently, new cases of the disease were detected, using a hospital registration system, to December 1974. One hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 6 publications
5
76
1
Order By: Relevance
“…All these results taken together strongly favor the hypothesis that Ag85 is also a protective antigen in infection with M. ulcerans and that Ag85 could indeed be used in a vaccine against Buruli disease. The fact that several studies have demonstrated a protective role of BCG vaccination against Buruli disease is also in accordance with these findings (5,23,26).…”
Section: Discussionsupporting
confidence: 78%
“…All these results taken together strongly favor the hypothesis that Ag85 is also a protective antigen in infection with M. ulcerans and that Ag85 could indeed be used in a vaccine against Buruli disease. The fact that several studies have demonstrated a protective role of BCG vaccination against Buruli disease is also in accordance with these findings (5,23,26).…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, there are several lines of evidence implicating CMI and delayed-type hypersensitivity responses in human M. ulcerans infections, favoring the possible existence of a phase of intracellularity of the pathogen, as follows. Studies with humans show that resistance to M. ulcerans is associated with the Th1 (24,25,26,55,76), while a shift to a Th2 phenotype is related to susceptibility (26), and point to a protective effect of BCG vaccination (46,53,54,63,66,73). Additionally, as BU disease progresses to healing, granuloma formation occurs (30,31,35,40,49,66,74), and the burulin skin test (65) tends to change from negative to positive (13,42).…”
Section: Discussionmentioning
confidence: 99%
“…Protection against M. ulcerans infection is provided by wearing long pants (335). Previous mycobacterial infection, evidenced by a tuberculin reaction of less than 4 mm, offers some protection against M. ulcerans disease (467). Protection is equivalent to that afforded by BCG vaccination (467).…”
Section: Risk Factors For M Ulcerans Infectionmentioning
confidence: 99%